2015
DOI: 10.1038/ncomms7260
|View full text |Cite
|
Sign up to set email alerts
|

Escape from crossover interference increases with maternal age

Abstract: Recombination plays a fundamental role in meiosis, ensuring the proper segregation of chromosomes and contributing to genetic diversity by generating novel combinations of alleles. Here, we use data derived from direct-to-consumer genetic testing to investigate patterns of recombination in over 4,200 families. Our analysis reveals a number of sex differences in the distribution of recombination. We find the fraction of male events occurring within hotspots to be 4.6% higher than for females. We confirm that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
122
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(144 citation statements)
references
References 21 publications
17
122
2
Order By: Relevance
“…As the definition of an event is based solely on proximity of gene converted mpps, we cannot discern whether the gene converted mpps within the same long event occurred simultaneously in a single process or in several collocated processes. Crossover interference has recently been shown to decrease with maternal age 42 , possibly leading to double crossover recombination events which in our study design could be detected as long NCO events. The complex nature of long NCO events and their GC bias make it unlikely that crossover interference explains a large fraction of long NCO events (cf.…”
Section: Discussionmentioning
confidence: 79%
“…As the definition of an event is based solely on proximity of gene converted mpps, we cannot discern whether the gene converted mpps within the same long event occurred simultaneously in a single process or in several collocated processes. Crossover interference has recently been shown to decrease with maternal age 42 , possibly leading to double crossover recombination events which in our study design could be detected as long NCO events. The complex nature of long NCO events and their GC bias make it unlikely that crossover interference explains a large fraction of long NCO events (cf.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, the crossover rate appears to increase with advancing maternal age. Specifically, more crossovers are detected in children born to older mothers, implying that oocytes that give rise to viable offspring in older mothers tend to have more crossovers (Kong et al 2004;Coop et al 2008;Campbell et al 2015;Ottolini et al 2015). Extra crossovers are proposed to buffer against the effects of advancing maternal age, in particular, the erosion of sister-chromatid cohesion (discussed below).…”
Section: Clinical Significance Of Meiotic Recombinationmentioning
confidence: 99%
“…Thus, crossover rate may be under selection in human populations. Both common and rare human alleles have now been linked to heritable variation in crossover rate (Stefansson et al 2005;Kong et al 2008Kong et al , 2014Chowdhury et al 2009;Fledel-Alon et al 2011;Campbell et al 2015). These include alleles of genes known to regulate meiotic recombination: the crossover regulators, RNF212, HEI10 (CCNB1IP1), and MSH4 (described above); RAD21L and REC8, which encode meiosis-specific cohesin subunits (Uhlmann 2011); and the DSB regulator, PRDM9 .…”
Section: Clinical Significance Of Meiotic Recombinationmentioning
confidence: 99%
“…Conversely, the influence of age on male meiotic recombination remains controversial. Some human studies reported decreased recombination rates in older men compared to younger ones [Sun et al, 2006], but comparable analyses in mice revealed opposite results [Vrooman et al, 2014], or an absence of effect Shi et al, 2002;Sun et al, 2005;Campbell et al, 2015]. For practical reasons, all these results were obtained by comparing samples from different individuals of different ages.…”
Section: Intraindividual Variation Of Meiotic Recombination Parametermentioning
confidence: 94%
“…Aging is a factor likely to influence intraindividual variation of meiotic recombination. The influence of age on aneuploidy has been thoroughly studied in humans [Hassold and Hunt, 2001;Campbell et al, 2015], as well as in mice [Vrooman et al, 2014]. In these species, an increasing risk of aneuploidy related to aging has been unequivocally demonstrated in female meiosis, which might be explained by a decreased recombination in older females.…”
Section: Intraindividual Variation Of Meiotic Recombination Parametermentioning
confidence: 99%